Herbicides That Target Acetohydroxyacid Synthase Are Potent Inhibitors of the Growth of Drug-Resistant Candida auris - Agnew-Francis, Kylie A.; Tang, Yucheng; Lin, Xin; Low, Yu Shang; Wun, Shun Jie; Kuo, Andy; Elias, S.M.A. Sayeed Ibn; Lonhienne, Thierry; Condon, Nicholas D.; Pimentel, Bruna N. A. S. [UNESP]; Vergani, Carlos E. [UNESP]; Smith, Maree T.; et al. (American Chemical Society (ACS), 2020)
Acetohydroxyacid synthase (AHAS, EC 2.2.1.6), the first enzyme in the branched chain amino acid biosynthesis pathway, is the target for more than 50 commercially available herbicides, and is a promising target for antimicrobial drug discovery. Herein, we have expressed and purified AHAS from Candida auris, a newly identified human invasive fungal pathogen. Thirteen AHAS inhibiting herbicides have Ki values of <2 μM for this enzyme, with the most potent having Ki values of <32 nM. Six of these compounds exhibited MIC50 values of <1 μM against C. auris (CBS10913 strain) grown in culture, with bensulfuron methyl (BSM) being fungicidal and the most potent (MIC50 of 0.090 μM) in defined minimal media. The MIC50 value increases to 0.90 μM in media enriched by the addition of branched-chain amino acids at the expected concentration in the blood serum. The sessile MIC50 for BSM is 0.6 μM. Thus, it is also an excellent inhibitor of the growth of C. auris biofilms. BSM is nontoxic in HEK-293 cells at concentrations >100 μM and thus possesses a therapeutic index of >100. These data suggest that targeting AHAS is a viable strategy for treating C. auris infections.
Keywords: AHAS inhibitor; biofilms.; Candida auris; herbicides; pathogenic fungus